Prognostic values of preoperative platelet-to-lymphocyte ratio, albumin and hemoglobin in patients with non-metastatic colon cancer - Li Z; Xu Z; Huang Y; Zhao R; Cui Y; Zhou Y; Wu X (Cancer Management and Research, 2019)
Zhigui Li,1 Zhaofen Xu,2 Yuqian Huang,1 Rui Zhao,1 Yaping Cui,1 Yong Zhou,1 Xiaoting Wu11Department of Gastrointestinal Surgery, West China Hospital, Sichuan University, Chengdu, Sichuan 610041, People’s Republic of China; 2Department of Pathology, The Second People’s Hospital, Neijiang, Sichuan 641000, People’s Republic of ChinaPurpose: Preoperative platelet-to-monocyte ratio (PLR), albumin and hemoglobin are suggested prognostic indicators in various malignancies. However, the prognostic values of PLR, albumin and hemoglobin remain elusive. The objective of the present study was to evaluate the prognostic values of PLR, albumin and hemoglobin in stage I-III colon cancer.Patients and methods: A total of 312 patients with non-metastatic colon cancer undergoing curative resection were enrolled in this study. The prognostic values of PLR, albumin and hemoglobin were identified by receiver operating characteristics, and univariate and multivariate analyses.Results: Univariate analysis revealed that preoperative PLR, albumin and hemoglobin were significantly associated with overall survival (OS) and that preoperative PLR and albumin were significantly associated with progression-free survival (PFS). Multivariate analysis revealed that preoperative PLR was significantly associated with OS.Conclusion: Reduced preoperative PLR was significantly associated with better OS in patients with stage I-III colon cancer. Preoperative PLR was an independent prognostic indictor for OS in patients with colon cancer undergoing curative resection.Keywords: platelet-to-lymphocyte ratio, albumin, hemoglobin, colon cancer, prognosis